A Review of Human Exposure to Microplastics and Insights Into Microplastics as Obesogens - Kannan, Kurunthachalam; Vimalkumar, Krishnamoorthi (Frontiers in Endocrinology, 2021)
The ubiquitous exposure of humans to microplastics (MPs) through inhalation of particles in air and ingestion in dust, water, and diet is well established. Humans are estimated to ingest tens of thousands to millions of MP particles annually, or on the order of several milligrams daily; studies have reported MP exposures of up to 100 mg daily. Biomonitoring studies of human stool, fetus, and placenta provide direct evidence of MP exposure in infants and children. MPs <20 µm can cross biological membranes. Whereas exposure to MPs itself is a concern, MPs can also be sources of exposure to plastic additives and other toxicants. Exposure of human cell lines to MP additives such as phthalates, bisphenols, and organotins causes adverse effects through the activation of nuclear receptors, peroxisome proliferator-activated receptors (PPARs) α, β, and γ, and retinoid X receptor (RXR), leading to oxidative stress, cytotoxicity, immunotoxicity, thyroid hormone disruption, and altered adipogenesis and energy production. In laboratory animal studies, maternal exposure to MPs altered energy and lipid metabolism in offspring and subsequent generations. Moreover, concomitant with the global increase in plastics production, the prevalence of overweight and obesity in human populations has increased over the past five decades, and there is considerable evidence to support the hypothesis that MPs and their additives are potential obesogens and that MP exposure is linked to the increasing prevalence of obesity/overweight globally. Even though MP exposures are ubiquitous and toxic effects from such exposures are increasing, systematic studies on this topic remain urgently needed.